Developing an Integrated Pest Management Program for Tomatoes in The Red River Delta of Vietnam: A mini review - Tuan M. Ha (Graduate Program of Syiah Kuala University, 2015)
Ecologically based approaches to pest management in crop production have been embraced in recent decades due to their validity and effectiveness. Integrated Pest Management (IPM) is not a new concept. It has been adopted in various regions in Vietnam, particularly in tomato production, an economically important vegetable crop in the Red River Delta (RRD). Given the occurrence and development of tomato pests are influenced by many factors such as soil types, crop varieties and growth habits, production practices, local climatic conditions, and growing seasons, this paper therefore developed an IPM program for tomatoes in the RRD based on the defined major pests in the region. Detailed factsheets for six major pests were developed and different components of the IPM were explored and employed for the ease of identification and management. Practical suggestions for tomato growers were also presented.